CHANCE DEVELOPMENTS: BINGO REGULATION IN BRAZIL - Jobim, Maria Luiza Kurban; Williams, Toni (Análise Econômica, 2017)
Throughout the neoliberalism era states have adopted policies that are often – and aptly — analysed and critiqued by reference to gambling metaphors. But the ways that states have turned to gambling industries to generate income, support community projects and promote economic and social development have received much less attention in critical political economy and policy discussion. This oversight is striking because many non-Islamic states have overturned (or greatly attenuated) historic prohibitions on the provision of games of chance over the past couple of decades, and some have sponsored gambling industries and products to foster community regeneration and sustainable development. Brazil, a country known for strong competitive traditions in sports and gaming, creative approaches to community economic development, and an urgent need to strengthen its public finances, is a notable exception to this liberalisation trend. This stance is interesting because Brazil liberalised its gambling regime in 1993 to allow non-state providers to operate bingo games. Drawing on the case of bingo regulation this paper critically analyses challenges that the Brazilian state encountered when it sought to create an economy of non-state provision of gambling products in aid of social development and the conflicts that have ensued as it has re-imposed repression of bingos. The paper reports on desk research and interviews conducted for the Bingo Project, an ESRC-funded comparative research project that critically examines bingo regulation in different parts of the world.